Training on Solid Medical Waste Management at Private Hospitals in Medan City - Setia Megawati Hutajulu; Nuraini Nuraini (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Inadequate management of solid medical waste poses potential risks of infection transmission, exposure to hazardous materials, and environmental damage. This study aims to evaluate the impact of training programs on enhancing nurses' knowledge, attitudes, and practices related to solid medical waste management. The research employed a quasi-experimental design with a pre-test and post-test approach, without a control group. A total of 38 inpatient nurses served as the research respondents. The results demonstrated significant improvements in the mean scores: knowledge increased by 3.342 points (t = 6.374; p = 0.000), attitude by 13.026 points (t = 8.525; p = 0.005), and practice by 2.079 points (t = 5.370; p = 0.001). All outcomes showed statistical significance (p < 0.05), and the 95% confidence interval indicated substantial and consistent improvements. Structured training programs have proven effective in developing nurses' competencies, especially when supported by adequate environmental literacy and strong management commitment. These findings underscore the importance of ongoing training as a strategic approach to improve the quality of solid medical waste management in hospitals.